Italy : Background Economic Developments and Issues - Supplementary Information Appendices. (IMF Staff Country Reports; Country Report ;, 1995)
This paper reviews the flaws of the Italian tax system during the 1990s and the rationale for reform. The paper highlights that a fundamental reform of the tax system took place in 1971-73, and introduced three main innovations: the concentration of tax authority almost exclusively at the level of the central government; a value-added tax, in line with the rest of the European Union; and the extension of the base of the personal income tax to additional income categories. This paper also reviews the management of public spending in Italy.